Environmental impact and nutrient adequacy of derived dietary patterns in Vietnam - Nguyen, Son D.; Biesbroek, Sander; Le, Tuyen D.; Feskens, Edith J. M.; Brouwer, Inge D.; Talsma, Elise F (Frontiers Media, 2023)
Rationale and objective: Improving diet quality while decreasing environmental impacts is an important challenge for a healthy and sustainable food system. Therefore, this study aims to analyze the most common dietary patterns per female household member and explore the diet quality and environmental impacts of these patterns.